Enhanced adsorption performance of sulfamethoxazole and tetracycline in aqueous solutions by MgFe2O4-magnetic biochar - Yu Deng; Min Wang; Yunpeng Yang; Xiaodong Li; Wenqing Chen; Tianqi Ao (Water Science and Technology, 2022)
Biochar has been reported as an excellent adsorbent for antibiotics, but the application faces the challenges of complicated separation. Here, MgFe2O4-magnetic biochars (MBCs) derived from corncob were synthesized at 300 °C to remove sulfamethoxazole (SMX) and tetracycline (TC) simultaneously. The characteristics of MBC300 had a high magnetic intensity. MBC300 had the maximum adsorption capacity of SMX with 50.75 mg/g and the high adsorption amount of TC with 120.36 mg/g respectively, which were 4.49 and 6.48 times those of BC300. MBC300 had the advantage of energy conservation compared with MBC450 and MBC600. The better fitting kinetics and isotherms indicated that the SMX and TC sorption onto MBC300 were governed by chemisorption. FTIR and XPS analyses confirmed that the SMX sorption onto MBC300 was dominated by polar interactions and π-π electron donor-acceptor interactions (π-π EDA). Furthermore, the TC sorption was involved in pore filling, π-π EDA, H-bonds, and surface complexation. MBC300 presented effective adsorption of SMX and TC over a wide range of pH. The competition between antibiotics and coexisting pollutants of dissolved organic matter (DOM), Ca2+, CO32−, and PO43− significantly inhibited the sorption. The results indicate that MBC300 is an effective and promising adsorbent to treat SMX and TC simultaneously. HIGHLIGHTS MgFe2O4-magnetic biochar prepared at low temperature (300 °C) had good magnetic intensity.; MBC300 had the highest adsorption capacity of SMX.; SMX sorption was dominated by polar interactions and π-π EDA.; TC sorption was involved in pore filling, π-π EDA, H-bonds, and surface complexation.;